Impact of COVID-19 pandemic on the pediatric services of a tertiary care hospital in North India: A retrospective review - Gera, Akriti; Singh, Amitabh; Sungadhi, Nidhi; Aggarwal, Nidhi; Gera, Rani (Indian Journal of Child Health, 2020)
Background: The novel coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has affected the world at large. To control the spread of the virus, the Government of India promoted simple measures such as social distancing and hand hygiene. Yet, the most prominent one was a strict nationwide lockdown on all non-essential services and complete curtailment of the public transport. Objective: Our study aims to quantify the impact of COVID-19 pandemic and lockdown measures on the pediatric services of a tertiary care center in North India. Materials and Methods: A retrospective observational study was done to analyze the change in our outpatient visits, admissions, and number of institutional deliveries, immunization services, pediatric surgeries, and mortality rates during the lockdown period when compared to the pre-lockdown period. Data of all children aged 0–12 years who presented to the pediatric medicine and pediatric surgery departments were collected. Data were divided into two groups; January 1, 2020–March 31, 2020 and April 1, 2020–June 30, 2020. Results: There was a reduction of 79.1% OPD attendance and 70.8% in immunization visits. Inpatient admission in pediatrics medicine and surgery decreased by 59.8% and 67.6%, respectively. The mortality rate increased from 11.8% to 13% and 7.6% to 19.6%, respectively. Emergency area visits decreased by 55.3% with an increase in mortality rate from 2.4% to 6.2%. Intramural births decreased by 55.4%. Conclusion: The COVID-19 pandemic has led to an unmet need of pediatric services. This requires urgent management or else it may halt the progress made in different aspects of health care.